Trải nghiệm du lịch y tế và hành vi truyền miệng của du khách: Nghiên cứu thực nghiệm tại Thành phố Hồ Chí Minh thông qua mô hình SOR - Tô Phước, Hải; Võ Xuân, Vinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Amid the growing prominence of medical tourism in emerging economies, this study investigates the effects of medical tourism experiences on tourists’ affective and behavioral responses, including happiness, perceived value, destination attachment, and word-of-mouth intentions. Drawing on the Stimulus–Organism–Response (SOR) framework, the study collected data from 454 domestic and international tourists in Ho Chi Minh City using structured questionnaires with five-point Likert scales. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed via SmartPLS 3 to test the hypothesized relationships. Findings reveal that positive medical tourism experiences significantly enhance tourists’ happiness and perceived value, which in turn promote destination attachment and word-of-mouth communication. The study contributes to tourism behavior theory by clarifying the emotional and cognitive pathways linking service experiences to post-consumption behaviors in the medical tourism context. Managerially, the results offer actionable implications for hospitals, tour operators, and wellness providers seeking to design emotionally engaging services that foster loyalty and organic promotion.
Keywords: Medical tourism experience; Tourist happiness; Place attachment; Word of mouth